37.6k views
4 votes
Solve for x:
4(1 - x) + 2 x=-3( x + 1)

User Giladd
by
5.1k points

1 Answer

7 votes

Answer:

x= -7

Explanation:

Simplify both sides of the equation.

4(1−x)+2x=−3(x+1)

(4)(1)+(4)(−x)+2x=(−3)(x)+(−3)(1)(Distribute)

4+−4x+2x=−3x+−3

(−4x+2x)+(4)=−3x−3(Combine Like terms)

Add 3x to both sides.

−2x+4+3x=−3x−3+3x

x+4=−3

Subtract 4 from both sides.

x+4−4=−3−4

x=−7

User Gorets
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.